Between the metropolis and the average city: the complexity of spatial interactions and central dynamics of Castanhal city in northeastern Pará - Ribeiro, Willame de Oliveira (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2016)
The city of Castanhal, Northeast of Pará, has roles of great complexity in the regional urban network, due to its localization in the intermediation between the metropolitan reality and the centrality of an average city, exercised in Northeastern Pará. Therefore, this article aims to reflect on the following matter: What are the roles played by the city of Castanhal in Northeastern Pará State before the process of metropolitan dispersion of Belém? From the construction of the theoretical framework, documentary surveys and field surveys it was found that the complexity of spatial interactions is a major feature of Castanhal, which is constituted as a hybrid city, having a metropolitan dimension and an average city size.